NUTRITIONAL AND INDUSTRIAL POTENTIALS OF ROSELLE (Hibiscus Sabdariffa L) AND BAOBAB (Adansonia Digitata) - Seweh, E. A.; Xiaobo, Z.; Bart-Plange, A.; Abubakari, M. (UDS International Journal of Development, 2019)
This study was conducted to investigate the industrial and nutritional potentials of under-utilised Roselle and Baobab seeds from Ghana. Proximate compositions and the physicochemical properties of their oil were compared to conventional oilseeds. The results of the proximate analyses showed that moisture contents of the seeds were very low. The fat, protein and fibre contents were relatively high suggesting that the seeds are excellent economic sources of oil for industrial, pharmaceutical and domestic usage. Physicochemical properties of the oil extracted from the seedsâ€™ powders using Soxhlet extractor revealed that the colour of roselle seed oil (RSO) was yellow while that of baobab seed oil (BSO) was dark brown. At room temperature, both oils were liquid. The low free fatty acid and peroxide values make the seeds and the oil suitable for human consumption.Â Â The results compared favourably with other premium vegetable oils and were within the ranges set by FAO/WHO. This research has contributed additional information to the recent call for research on alternative, novel and under-utilised sources of vegetable oil for domestic and industrial applications. Â Keywords:Â Nutritional and Industrial potential, Under-utilised seeds, Proximate composition, Physicochemical properties, Baobab, Roselle.